A wide range of South American inselberg floras reveal cohesive biome patterns - Barbosa-Silva, Rafael Gomes; Andrino, Caroline O.; Azevedo, Luísa; Lucresia, Luísa; Lovo, Juliana; Hiura, Alice L.; Viana, Pedro L.; Giannini, Tereza C.; Zappi, Daniela Cristina (Frontiers in Plant Science, 2022)
Inselbergs are azonal formations found scattered in different biomes globally. The first floristic list focusing on an inselberg in the Brazilian Amazon is presented here. We aimed to investigate floristic and phylogenetic connections among Neotropical inselbergs and analyze whether environmental variables act as a filter of plant lineages. We used a database compiled from 50 sites spanning three main Neotropical biomes (Amazon, 11 sites, Atlantic Forest, 14 sites, and Caatinga, 25 sites) comprising 2270 Angiosperm species. Our data highlight the vastly different inselberg flora found in each biome. The inselberg floras of the Atlantic Forest and Caatinga show closer phylogenetic ties than those seen in the other biome pairs. The phylogenetic lineages found in all three biomes are also strongly divergent, even within plant families. The dissimilarity between biomes suggests that distinct biogeographical histories might have unfolded even under comparable environmental filtering. Our data suggest that the inselberg flora is more related to the biome where it is located than to other factors, even when the microclimatic conditions in the outcrops differ strongly from those of the surrounding matrix. Relative to the other biomes, the flora of the Caatinga inselbergs has the highest level of species turnover. There is a possibility that plants colonized these rather distant inselbergs even when they were found under very different climatic conditions than those in the Amazonian and Atlantic Forest biomes. It is worth noting that none of the studied inselbergs found in the Caatinga biome is protected. In view of the uniqueness and drought-resilient lineages present in each group of inselbergs, along with their vulnerability to destruction or disturbance and their strong connection with water availability, we stress the need to protect this ecosystem not only to conserve plants potentially useful for ecological restoration but also to preserve the balance of this ecosystem and its connections.